2006
DOI: 10.1007/s11262-005-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome comparison of a novel classical swine fever virus isolated in China in 2004 with other CSFV strains

Abstract: The genome of a novel classical swine fever virus (CSFV), SWH/CA/2004, isolated from a hog pen in Henan Province, central China, is 12,296 nucleotides (nt) in length. It is composed of a 373-nt 5' terminal non-translated region (NTR), a 11,697-nt open reading frame (ORF) encoding a polyprotein of 3,898 amino acids (aa), and a 226-nt 3'-NTR. Genome comparison of the SWH/CA/2004 isolate (GenBank Accession: DQ127910) with other known CSFV isolates was performed and analyzed. Corresponding segments from SWH/CA/200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
1
24
1
Order By: Relevance
“…Two CSFV isolates (CSFV-PY-2009 and CSFV-NH-2009) collected from Hainan were closely related to the SWH and cF114 Chinese strains, while only one strain (CSFV-JY-2010) A previous study showed that seven Chinese CSFV isolates from six provinces, including Guangxi, Guizhou, Shanxi, Jilin, Qinghai, and Xizang, were grouped together with the Shimen reference strain in subgroup 1.1 [25]. Li et al [26] indicated that the SWH isolate was closely related to the highly virulent isolate, cF114, and deduced that it belonged to the highly virulent isolate group. In our study, the 13 CSFV isolates cluster together with Shimen, SWH, and cF114, only one CSFV isolate was placed closely to Alfort 187, while they were distant from the vaccine strain (hog cholera lapinized virus) HCLV.…”
Section: Resultsmentioning
confidence: 98%
“…Two CSFV isolates (CSFV-PY-2009 and CSFV-NH-2009) collected from Hainan were closely related to the SWH and cF114 Chinese strains, while only one strain (CSFV-JY-2010) A previous study showed that seven Chinese CSFV isolates from six provinces, including Guangxi, Guizhou, Shanxi, Jilin, Qinghai, and Xizang, were grouped together with the Shimen reference strain in subgroup 1.1 [25]. Li et al [26] indicated that the SWH isolate was closely related to the highly virulent isolate, cF114, and deduced that it belonged to the highly virulent isolate group. In our study, the 13 CSFV isolates cluster together with Shimen, SWH, and cF114, only one CSFV isolate was placed closely to Alfort 187, while they were distant from the vaccine strain (hog cholera lapinized virus) HCLV.…”
Section: Resultsmentioning
confidence: 98%
“…The disease has been eradicated in several countries or under control in other countries. Sporadical outbreaks were reported in the Americas and Asia as well as some European countries during the past few years [3,4,[10][11][12][13][16][17][18][19]. To control the disease in endemic areas, live attenuated C-strain vaccine has been proven to be efficacious and safe [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses performed in different parts of the world confirmed that CSF virus isolates that differ by genetic typing seem to be characteristic for certain geographic regions (Bartak and Greiser-Wilke, 2000;Blacksell et al, 2005;Chen et al, 2008;Arce et al, 2005;Kamakawa et al, 2006;Li et al, 2006;Pereda et al, 2005;Sabogal et al, 2006;Stadejek et al, 1997;Vilcek et al, 1997).…”
Section: -140mentioning
confidence: 95%